MANAJEMEN STOK PANGAN RUMAH TANGGA PETANI PADI ANGGOTA LUMBUNG PANGAN DI KECAMATAN AMBARAWA KABUPATEN PRINGSEWU - Arifatuzzakiyah, Maula; Prasmatiwi, Fembriarti Erry; Firdasari, Firdasari (Lampung University, 2024)
This study aimed firstly to analyze the management of household food stocks and secondly to analyze the various factors affecting household food stocks for rice farmers. All rice farmers were members of the food barn in Ambarawa Sub-district, Pringsewu District. The samples were selected by simple random sampling consisting of 7 granaries with a total of 70 members. The data were collected from January to February 2023. To obtain the first objective, the data were analyzed by using the calculation of food stocks referring to the Chafid equation formula (2017), i.e. the amount of food inventory was subtracted by its sale quantity and its utilization. To obtain the second objective, the data were analyzed by using the multiple linear regression. The results showed that the food stocks of rice farmers who were members of the food barn were 573 kg of MDG in the first season and 450 kg of MDG in the second season, which were not an ideal amount for food stock. This was because the ideal amounts of needs were 586.93 kg of MDG for the first season and 591.51 kg of MDG for the second season. Some of the factors affecting the food stock of the rice farming households incorporated in food barns were land area and household income. Key words: regression analysis, sale delay analysis, stocks, storage.